A rare case of a solitary laryngeal xanthoma and its clinical implications in a developing country like India - Basavarajaiah, Bharathi Murundi; De, Kumar Shankar; Suryanarayan Rao, Rakesh Bambore; Rudrappa, Babu Ambale (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
We present a rare case of a solitary laryngeal xanthoma in a 42 year old male, with complaints of hoarseness and change in voice since1 year. Direct laryngoscopic examination revealed a smooth textured polyp like mass arising from anterior 1/3rd of left vocal cord. No other similar lesions were noted anywhere else on his body. Microlaryngeal excision of mass was done and sent for histopathological examination, which showed fragments of stratified squamous epithelium with sub-epithelium displaying sheets of foamy cells. Immunohistochemistry was positive for CD68 and a diagnosis of solitary laryngeal xanthoma was arrived at. Follow up of the patient showed no recurrence but investigations revealed dyslipidemia, which was newly detected. Hence a diagnosis of a solitary laryngeal xanthoma, even without any other lesions, warrants a thorough investigative workup, including lipid profile, even in patients who are not known cases of dyslipidemia. This becomes especially important in a country like India, where a large number of cases of dyslipidemia go undetected; leading to atherosclerosis and even cardiac events in the future.